Jane Joseph & Guy Poltock. Fit for a Queen. A recipe book researched from the handwritten manuscripts of Ada Parsons (1888-1958) head cook to the Earl of Strathmore c.1912 to 1916 - Jaine, Tom (Petits Propos Culinaires, 2012)
Jane Joseph & Guy Poltock. Fit for a Queen. A recipe book researched from the handwritten manuscripts of Ada Parsons (1888-1958) head cook to the Earl of Strathmore c.1912 to 1916: Cranfield University Press, 2011, 150pp., hardback, £35.00.